Are Old People Merited Veterans of Society? Some notes on a Problematic Claim - Jönson, Håkan; Nilsson, Magnus (Outlines. Critical Practice Studies, 2007)
The article shows how merit has been used to highlight pensioners as a special population in the claims-making activities of the senior rights movement in Sweden, as well as in debates about issues concerning old age. Simply put, merit refers to the claim that pensioners have built the society and they are entitled to special treatment – for instance welfare, reverence – for this reason. Merit is concluded to be a rhetorical tool with the potential of countering images of older people as a burden to the young. It portrays seniors as a population worthy of welfare and reverence. Social movements that emphasize merit among seniors will however risk isolation, since such claims to some extent have become associated with populist attacks on immigrants, politicians and other groups labeled as non-merited.